Applicazione della neurodiagnostica avanzata allo studio dei disturbi psicologici nelle malattie infiammatorie croniche intestinali - Agostini, Alessandro <1973> (Alma Mater Studiorum - Università di Bologna, 2011)

(untitled)
Background and aim Ulcerative Colitis (UC) and Crohn’s Disease (CD), collectively labelled as inflammatory bowel disease (IBD), are idiopathic, chronic inflammatory disorder of the bowel with a remitting and relapsing course. IBD are associated to poor emotional functioning and psychological distress. We have investigated the brain involvement in patients with IBD using functional magnetic resonance imaging (fMRI). Materials and methods We developed an emotional visual task to investigate the emotional functioning in 10 UC patients and 10 healthy controls (HC). Furthermore, we have compared the brain stress response between a group of 20 CD patients and a group of 18 HC. Finally, we evaluated potential morphological differences between 18 CD patients and 18 HC in a voxel based morphometry (VBM) study. Results We found brain functional changes in UC patients characterized by decreased activity in the amygdala in response to positive emotional stimuli. Moreover, in CD patients, the brain stress response and habituation to stressful stimuli were significantly different in the medial temporal lobe (including the amygdala and hippocampus), the insula and cerebellum. Finally, in CD patients there were morphological abnormalities in the anterior mid cingulated cortex (aMCC). Conclusion IBD are associated to functional and morphological brain abnormalities. The previous intestinal inflammatory activity in IBD patients might have contributed to determine the functional and morphological changes we found. On the other hand, the dysfunctions of the brain structures we found may influence the course of the disease. Our findings might have clinical implications. The differences in the emotional processing may play a role in the development of psychological disorders in UC patients. Furthermore, in CD patients, the different habituation to stress might contribute to stress related inflammatory exacerbations. Finally, the structural changes in the aMCC might be involved in the pain symptoms associated to the bowel disorder.